Similar pattern, different paths: tracing the biogeographical history of Megaloptera (Insecta: Neuropterida) using mitochondrial phylogenomics. (24th November 2021) - Jiang, Yunlan; Yue, Lu; Yang, Fan; Gillung, Jessica P.; Winterton, Shaun L.; Price, Benjamin W.; Contreras‐Ramos, Atilano; Hayashi, Fumio; Aspöck, Ulrike; Aspöck, Horst; Yeates, David K.; Yang, Ding; et al.
Abstract: The sequential breakup of the supercontinent Pangaea since the Middle Jurassic is one of the crucial factors that has driven the biogeographical patterns of terrestrial biotas. Despite decades of effort searching for concordant patterns between diversification and continental fragmentation among taxonomic groups, increasing evidence has revealed more complex and idiosyncratic scenarios resulting from a mixture of vicariance, dispersal and extinction. Aquatic insects with discreet ecological requirements, low vagility and disjunct distributions represent a valuable model for testing biogeographical hypotheses by reconstructing their distribution patterns and temporal divergences. Insects of the order Megaloptera have exclusively aquatic larvae, their adults have low vagility, and the group has a highly disjunct geographical distribution. Here we present a comprehensive phylogeny of Megaloptera based on a large‐scale mitochondrial genome sequencing of 99 species representing >90% of the world genera from all major biogeographical regions. Molecular dating suggests that the deep divergence within Megaloptera pre‐dates the breakup of Pangaea. Subsequently, the intergeneric divergences within Corydalinae (dobsonflies), Chauliodinae (fishflies) and Sialidae (alderflies) might have been driven by both vicariance and dispersal correlated with the shifting continent during the Cretaceous, but with strikingly different and incongruent biogeographical signals. The austral distribution of many corydalids appears to be a result of colonization from Eurasia through southward dispersal across Europe and Africa during the Cretaceous, whereas a nearly contemporaneous dispersal via northward rafting of Gondwanan landmasses may account for the colonization of extant Eurasian alderflies from the south.